Development of Monoclonal Antibodies to Detect for SARS-CoV-2 Proteins. Issue 10 (30th May 2022) - Mishra, Nawneet; Teyra, Joan; Boytz, RuthMabel; Miersch, Shane; Merritt, Trudy N.; Cardarelli, Lia; Gorelik, Maryna; Mihalic, Filip; Jemth, Per; Davey, Robert A.; Sidhu, Sachdev S.; Leung, Daisy W.; et al.
Graphical abstract: Highlights: Generated novel antibodies against SARS-CoV-2 proteins by phage display. Identified multiple monoclonal antibodies against >10 individual proteins from SARS-CoV-2. Characterized monoclonal antibodies by western blot analysis and immunofluorescence. Identified multiple antibodies with unique and non-overlapping epitopes. Abstract: The COVID-19 pandemic caused by SARS-CoV-2 infection has impacted the world economy and healthcare infrastructure. Key reagents with high specificity to SARS-CoV-2 proteins are currently lacking, which limits our ability to understand the pathophysiology of SARS-CoV-2 infections. To address this need, we initiated a series of studies to generate and develop highly specific antibodies against proteins from SARS-CoV-2 using an antibody engineering platform. These efforts resulted in 18 monoclonal antibodies against nine SARS-CoV-2 proteins. Here we report the characterization of several antibodies, including those that recognize Nsp1, Nsp8, Nsp12, and Orf3b viral proteins. Our validation studies included evaluation for use of antibodies in ELISA, western blots, and immunofluorescence assays (IFA). We expect that availability of these antibodies will enhance our ability to further characterize host-viral interactions, including specific roles played by viral proteins during infection, to acquire a better understanding of the pathophysiology of SARS-CoV-2 infections.